(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India’s economy is an agrarian economy and vegetables are being grown on a large scale in India along with various crops. The only one from the vegetable group is “Tomato”. Tomato is widely grown in India. China is the world’s largest producer of tomatoes, India is second largest. Tomatoes from India export their tomatoes to Pakistan, Bangladesh, Nepal and other countries in Asia. Similarly, in other states, tomatoes in Nashik district send a lot of reply to the North India. Example: Punjab, Haryana, Rajasthan, Madhya Pradesh, Gujarat etc. States are sent. In addition to various states of India, tomato crop has an important role in the rural economy’s rural economy.